Allopurinol dose escalation to achieve serum urate below 6 mg/dL: an open-label extension study. Issue 12 (22nd August 2017) - Stamp, Lisa K; Chapman, Peter T; Barclay, Murray; Horne, Anne; Frampton, Christopher; Tan, Paul; Drake, Jill; Dalbeth, Nicola
Abstract : Objectives: To determine the long-term safety and efficacy of allopurinol dose escalation (DE) to achieve target serum urate (SU) in gout. Methods: People, including those with chronic kidney disease, who completed the first 12 months of a randomised controlled trial continued into a 12-month extension study. Participants randomised to continue current dose for the first 12 months began allopurinol DE at month 12 if SU was ≥6 mg/dL (control/DE). Immediate DE participants who achieved target SU maintained allopurinol dose (DE/DE). The primary endpoints were reduction in SU and adverse events (AEs) at month 24. Results: The mean (SE) change in SU from month 12 to 24 was −1.1 (0.2) mg/dL in control/DE and 0.1 (0.2) mg/dL in DE/DE group (p<0.001). There was a significant reduction in the percentage of individuals having a gout flare in the month prior to months 12 and 24 compared with baseline in both groups and in mean tophus size over 24 months, but no difference between randomised groups. There were similar numbers of AEs and serious adverse events between groups. Conclusions: The majority of people with gout tolerate higher than creatinine clearance-based allopurinol dose and achieve and maintain target SU. Slow allopurinol DE may be appropriate in clinical practice even in those with kidney impairment. Trial registration number: ACTRN12611000845932